An Umbrella Review of E-Cigarettes’ Impact on Oral Microbiota and Biofilm Buildup - Beatriz Panariello; Fabrízio Dias Panariello; Ashminie Misir; Eliane Porto Barboza (Pathogens)
E-cigarettes, a form of electronic nicotine delivery system (ENDS), have gained significant popularity, particularly among adolescents who often view vaping as a “cool” lifestyle choice. This growing trend has spurred extensive research on the effects of ENDS on both oral and systemic health. By synthesizing data from systematic reviews and meta-analyses, this umbrella review offers a comprehensive evaluation of the impact of e-cigarettes on oral biofilm accumulation and microbiota composition. A systematic search was conducted up to 12 March 2025, across PubMed/MEDLINE, Google Scholar, Cochrane Library, and Scopus for studies published between 2015 and 2025. Ten studies met the eligibility criteria. The quality of the selected papers, as assessed using the AMSTAR 2 tool, ranged from moderate to high. The findings of this review suggest that e-cigarette use may contribute to dysbiosis in the oral microbiota and foster biofilm accumulation, thereby increasing the risk of oral diseases such as periodontitis, peri-implantitis, oral candidiasis, and caries. The findings also highlight the need for further research into the long-term effects of e-cigarette use on oral health. This review is registered with PROSPERO (CRD420251025639).